What is AI? Applications of artificial intelligence to dermatology. (29th March 2020) - Du‐Harpur, X.; Watt, F.M.; Luscombe, N.M.; Lynch, M.D.
Summary: In the past, the skills required to make an accurate dermatological diagnosis have required exposure to thousands of patients over many years. However, in recent years, artificial intelligence (AI) has made enormous advances, particularly in the area of image classification. This has led computer scientists to apply these techniques to develop algorithms that are able to recognize skin lesions, particularly melanoma. Since 2017, there have been numerous studies assessing the accuracy of algorithms, with some reporting that the accuracy matches or surpasses that of a dermatologist. While the principles underlying these methods are relatively straightforward, it can be challenging for the practising dermatologist to make sense of a plethora of unfamiliar terms in this domain. Here we explain the concepts of AI, machine learning, neural networks and deep learning, and explore the principles of how these tasks are accomplished. We critically evaluate the studies that have assessed the efficacy of these methods and discuss limitations and potential ethical issues. The burden of skin cancer is growing within the Western world, with major implications for both population skin health and the provision of dermatology services. AI has the potential to assist in the diagnosis of skin lesions and may have particular value at the interface between primary and secondary care. The emerging technology represents an exciting opportunity for dermatologists, who are the individuals best informed to explore the utility of this powerful novel diagnostic tool, and facilitate its safe and ethical implementation within healthcare systems. Abstract : What is already known about this topic? There is considerable interest in the application of artificial intelligence to medicine. Several publications in recent years have described computer algorithms that can diagnose melanoma or skin lesions. Multiple groups have independently evaluated algorithms for the diagnosis of melanoma and skin lesions. What does this study add? We combine an introduction to the field with a summary of studies comparing dermatologists against artificial intelligence algorithms with the aim of providing a comprehensive resource for clinicians. This review will equip clinicians with the relevant knowledge to critically appraise future studies, and also assess the clinical utility of this technology. A better informed and engaged cohort of clinicians will ensure that the technology is applied effectively and ethically. Plain language summary available online